Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0054-001 EXPORT ST/HP.345.HVT/FC/EK/398. Secretary's. 6th January, 1938. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, FOODSTUFFS FOR SPAIN. I thank you for your letter of the 5th January, from which I note that all available space on the s.s. Lucky has been booked and that they are unable to accept the proposed cargo of eighty tons of sugar. If, however, one ton of ships biscuits can be sent on the s.s. Madge Llewellyn from Liverpool and the insurance premium is not greatly in excess of ten guineas, we shall be glad if this small consignment can be dispatched. Yours sincerely, Assistant Secretary. 292/946/29/54